The Effect of Organizational Activity on Grade Point Average (GPA) in Medical Faculty of Indonesian Muslim University - El Firman, Andi Mappaita; Royani, Ida; Hamzah, Pratiwi Nasir; Makmun, Armanto; Aisyah, Windi Nurul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Competencies in medical education have been determined by the Indonesian Doctor Competency Standards (SKDI). One way that SKDI can be done is through academic learning processes (intracurricular) and student activities or organizational activities (extracurricular). However, many opinions state that extracurricular activities such as being active in organizations can have a negative impact on student achievement. This research aims to determine the relationship between organizational activity and the Grade Point Average of students at the Academic Stage of the Faculty of Medicine, Indonesian Muslim University class of 2020. This research design uses descriptive analytics with a cross-sectional approach. The sampling technique in this research used purposive sampling with 156 respondents. The data analysis used is the chi-square statistical test to determine the significance of the relationship between the independent variable and the dependent variable. To assess student organizational activity, a questionnaire is used as a tool which consists of 13 question indicators and then categorized as active and inactive students. Meanwhile, students' grade point averages will be categorized into satisfactory and unsatisfactory based on the set number limits. The research results showed that 149 samples (95.5%) were classified as active in participating in organizations and 144 samples (92.3%) had a GPA that was classified as satisfactory. Based on the research results, it was found that there was no significant relationship between organizational activity and the GPA of students at the academic stage of the class of 2020, Faculty of Medicine, Indonesian Muslim University, where the p-value = 0.503 (>0.05) with a weak correlation coefficient. Researchers recommend conducting further research on organizational activity variables, particularly on the effect between position or number of organizations joined and GPA, as well as the role of each organization in supporting the academics of its members.